Association of Air Pollutant Index (API) on SARS-CoV-2 of Coronavirus Disease 2019 (COVID-19) in Malaysia - Abdullah S.; Imran M.A.; Mansor A.A.; Yusof K.M.K.K.; Dom N.C.; Saijan S.K.; Yatim S.R.M.; Ahmed A.N.; Ismail M. (Korean Society for Atmospheric Environment, 2023)
atmospheric pollution; COVID-19; disease prevalence; infectious disease; vaccine; virus; Malaysia